Stochastic models - Institute for Operations Research and the Management Sciences (Monticello, NY : Marcel Dekker, Inc., 2001)
Print + Online from 1997-
Title from cover.
Published: Philadelphia, PA : Taylor & Francis, 2005-
Keywords: Stochastic processes -- Periodicals; Stocahastic Model; Stochastic Calculus